History of medicine : a scandalously short introduction - Duffin, Jacalyn (Toronto ; Buffalo : University of Toronto Press, 2021)
'Jacalyn Duffin's History of Medicine is one of the leading texts used to teach medical and nursing students the history of their profession. Emphasizing broad concepts rather than names and dates, it has also been widely used and appreciated in history courses and by general readers for more than twenty years. Based on sound scholarship and meticulous research, History of Medicine incorporates pithy examples from a range of periods and places and is infused with a characteristic wit. The third edition has been completely revised to highlight new scholarship on the past and incorporate significant medical events of the most recent decade--including new technologies, drug shortages, medical assistance in dying, and recent outbreaks of infectious diseases such as Ebola, H1N1, Zika, and COVID-19. The book is organized around themes of scientific and clinical interest, such as anatomy, physiology, pharmacology, surgery, obstetrics, medical education, health-care delivery, and public health. It includes a chapter on how to approach research in medical history, updated with new resources. History of Medicine is sensitive to the power of historical research to inform current health care practice and enhance cultural understanding.'--
Introduction: Heroes and Villains in the History of Medicine -- The Fabricated Body: History of Anatomy -- Interrogating Life: History of Physiology -- Science of Suffering: History of Pathology -- First Do No Harm: History of Treatment, Pharmacology, and Pharmaceuticals -- On Becoming and Being a Doctor: Education, Licensing, and Payment -- Plagues and Peoples: Epidemic Diseases in History -- Why Is Blood Special? Changing Concepts of a Vital Humor -- Technology and Disease: Stethoscopes, Hospitals, and Other Gadgets -- Work of the Hand: History of Surgery -- Women's Medicine and Medicine's Women: History of Obstetrics, Gynecology, and Women -- Wrestling with Demons: History of Psychiatry -- No Baby, No Nation: History of Pediatrics -- A Many-Faceted Gem: The Decline and Rebirth of Family Medicine -- When the Patient Is Plural: Public and International Health --'Slow as a Glacier, Equally Relentless': Patient-Centered Medicine -- Sleuthing and Science: How to Research a Question in Medical History.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on August 03, 2021).
WorldCat record variable field(s) change: 050
Keywords: Medicine -- History; Medicine; Electronic books; History